Perkembangan Nilai-Nilai Murni Melalui Pelajaran Sains dan Matematik - Jusoh, Ismail (Penerbit Universiti Sains Malaysia, 1987)
This article is on introduction concerning Issues of assismilatlng aesthetic values through the teaching of sciences and mathematics. The first part explains briefly t he meaning of aesthetic values. Then analogies based on situations that happed around us are given to explain the assimilation process in the above context. Basic preparations and the main characteristics for this formative process are discussed with references being made t hrough authoritative and authentic reasonings. References were also made to writings of authors who have lived to what they exponnded. They serve as examples for all of us.